2020
DOI: 10.3389/fmicb.2019.03094
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin A Is Essential in the Regulation of Asexual Development, Stress Responses and Pathogenesis in Talaromyces marneffei

Abstract: Talaromyces marneffei is a common cause of infection in immunocompromised patients in Southeast Asia and Southern China. The pathogenicity of T. marneffei depends on the ability of the fungus to survive the cytotoxic processes of the host immune system and grow inside host macrophages. These mechanisms that allow T. marneffei to survive macrophage-induced death are poorly understood. In this study, we examined the role of a calcineurin homolog (cnaA) from T. marneffei during growth, morphogenesis and infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…[96][97][98] and Pacoccidiodes brasiliensis [99]. Recent studies reveal a role of calcineurin in growth and virulence of T. marneffei [100]. In T. marneffei, deletion of the cnaA gene resulted in substantial defects in conidiation, germination, morphogenesis, cell wall integrity, and tolerance to several stresses.…”
Section: Iron and Calcium Are Essential Cations Required For Growth A...mentioning
confidence: 99%
“…[96][97][98] and Pacoccidiodes brasiliensis [99]. Recent studies reveal a role of calcineurin in growth and virulence of T. marneffei [100]. In T. marneffei, deletion of the cnaA gene resulted in substantial defects in conidiation, germination, morphogenesis, cell wall integrity, and tolerance to several stresses.…”
Section: Iron and Calcium Are Essential Cations Required For Growth A...mentioning
confidence: 99%
“…Amphotericin B is the rst-line drug recommended to treat T. marneffei [1]. Meanwhile, voriconazole is effective against T. marneffei [29][30][31][32][33]. Huang et al [30] reported similar response rates with voriconazole and amphotericin B as induction therapy for Talaromycosis in patients with HIV/AIDS, but voriconazole had a shorter induction time (11-13 days vs. two weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Exposures to 254 nm UV irradiation for 5, 10, and 15 min were also tested for UV resistance. All cultures were incubated for 14 days at 25°C.Based on references [ 10 , 18 ] and pre-experiments, the concentrations of KCl, H 2 O 2 , SNAP, menadione (VitK), and sorbitol were selected. The ability of melanin recovery in albino strains and pigmented strains were cultured on PDA with 50 mg/L tricyclazole at 25°C for 14 days.…”
Section: Methodsmentioning
confidence: 99%